Uma proposta de sistema de gestão integrado para unidades de triagem de resíduos sólidos urbanos - Hernandes, Alessandra Rosado (Universidade do Vale do Rio dos Sinos, 2011)
Due to population growth and consumption of disposable materials, an increase in environmental degradation, is the use of natural resources as raw material or for generating large quantities of waste. As an alternative to the problems related to the generation of waste, there are Units of Sorting of municipal solid waste - MSW. That they represent a solution to the waste of raw materials and energy used in the production of consumer materials would present difficulties in terms of administrative issues, internal conflicts, the unhealthy conditions of the workplace, lack of equipment and low wages. By analyzing the operating system of the units screening RSD Aturoi Vitoria and Nova Conquista of the Sao Leopoldo, compared to the tools of cleaner production, systems of quality management (SGQ), environmental management (SGA) and occupational health and safety (OHSAS) seek to propose an integrated management system adapted to their production processes. Thus, we standardize the activities developed in such centers in order to boost income by increasing productivity, as well as the greater control of potential environmental, health and welfare of the people involved. Through the methodology of cleaner production (P+L), we also encourage the reuse of waste little commercial interest as a raw material for the production and marketing of green goods, and encourage proper separation of recyclable waste in homes, encouraging the shipment to the recycling industry. As for the diagnoses made for associations Aturoi and Nova Conquista regarding the technical, organizational, environmental, economic and health at work, one can observe that the clubs have difficulties of various orders. Among them, ignorance as to the types of waste they receive (hazardous biological, chemical, etc.). The failure to record information about the manufacturing process, a short work day as well as some misunderstanding about the factors that can really influence productivity in their activities. through these results, the municipal bodies responsible for SGIRSU, are likely to promote beneficial changes and really required with the current management system of UTRSRDR, as well as ensuring the technical, administrative, financial, and social infrastructure.
Keywords: Engenharia civil; Degradação ambiental; Resíduos urbanos recicláveis; Unidades de triagem de resíduos sólidos urbanos; ACCNPQ::Engenharias::Engenharia Civil